Penguatan Literasi Numerasi Anak Pesisir Melalui Program Rumah Belajar Kolaboratif Bagi Siswa Sekolah Dasar Di Kabupaten Lombok Timur, Nusa Tenggara Barat - Hanifah Noviandari; Hilmi Yahya Al Musthofa (Lentera Salam Institute, 2026)
The numeracy literacy gap among coastal children represents a multidimensional structural problem, influenced by the socioeconomic conditions of fishing families, limited access to quality educational facilities, and the scarcity of community-based learning ecosystems. This community service study aims to describe the implementation of the Collaborative Learning House program based on the Service Learning approach and to analyze changes in numeracy literacy skills among elementary school students in East Lombok Regency, West Nusa Tenggara following the mentoring program. The activity was conducted on November 13, 2025, involving 50 students from grades III to VI in coastal areas. The Service Learning approach comprised five systematic phases: Preparation, Action, Reflection, Demonstration, and Celebration. Program evaluation employed Kirkpatrick's Four Levels of Evaluation integrated with Bloom's Taxonomy (cognitive C1–C6, affective A1–A5, and psychomotor P1–P5). Results indicated significant improvement across all dimensions: average cognitive ability increased from 37.0% to 70.5% (from Sufficient to Good category), affective dimension improved by an average of 34.8%, and psychomotor dimension showed an average increase of 37.5%. At the Kirkpatrick Reaction Level, participant enthusiasm increased by 35 percentage points, reaching the Excellent category. These findings confirm that a contextual, community-based Service Learning approach is effective in improving numeracy literacy among coastal children. The program also succeeded in building social capital through the establishment of a learning community with eight active volunteers as a sustainability initiative. The implications of these findings affirm the urgency of integrating community approaches into non-formal educational literacy program designs in marginalized areas.